Combined industrial olive oil extraction plant using ultrasounds, microwave, and heat exchange: Impact on olive oil quality and yield. (March 2019) - Tamborrino, Antonia; Romaniello, Roberto; Caponio, Francesco; Squeo, Giacomo; Leone, Alessandro
Abstract: In this study, an industrial combined plant (ICP) constructed from a low-frequency ultrasound device, microwave apparatus and heat exchanger is employed to investigate the real possibility of introducing these innovative technologies to the olive oil extraction process and evaluating their influence on olive oil quality and yield. The novelty of this study lies in the simultaneous use of these three technologies to condition the olive paste in a real olive oil extraction plant. Different olive paste treatments were compared in order to define the effects on the olive oil quality and yield. The use of a spiral heat exchanger in addition to the malaxer reduced the malaxation time to 20 min, and with the microwave apparatus it was possible to obtain an entirely continuous process, without interruptions, from the milling phase to the solid-liquid separation phase. The internal spiral aids in moving the paste from the input to output section, resulting in limited operating pressure. Using the ICP device led to an average increase in extractability ranging from 2.30 to 3.85% with respect to the control thesis, for the Arbosana and Arbequina varieties, respectively, but this difference was not statistically significant. Regarding the virgin olive oil (VOO) quality, the use of the ICP did not affect the marketable parameters and total phenol content, while in terms of the process efficiency, the ICP obtained a higher value than the conventional process and improved the extraction yield. Highlights: A spiral coil heat exchanger was developed to condition the olive paste. An industrial combined plant (ICP) was developed to condition the olive paste. Using combined plant an increase in extractability was found. Superior results in phenolic and compounds were found using ICP.